Minerals : A Very Short Introduction - Vaughan, David J., 1946- (Oxford, New York Oxford University Press, 2014)
Minerals existed long before any forms of life, playing a key role in the origin and evolution of life; an interaction with biological systems that we are only now beginning to understand. Exploring the traditional strand of mineralogy, which emphasizes the important mineral families, the well-established analytical methods (optical microscopy and X-ray diffraction) and the dramatic developments made in techniques over recent decades, David Vaughan also introduces the modern strand of mineralogy, which explores the role minerals play in the plate tectonic cycle and how they interact with the living world. Demonstrating how minerals can be critical for human health and illness by providing essential nutrients and releasing poisons, Vaughan explores the multitude of ways in which minerals have aided our understanding of the world
Include Illustration and Index
Keywords: Minerals -- Mineralogy